Dirāsah ‘an al-ghazw al-thaqāfiy wa al-hazīmah al-nafsiyyah - Saifullah Kamalie (Insaniyat : Journal of Islam and Humanities, 2016)
Indonesia  is  the  largest  Muslim  populations  in  the  world.  According  to  the 2011  census,  there was  about  eighty  eight  percentage  (nearly  two  hundred and  five  million  Muslims)  of  the  total population  of  this  country.  Does  this largest  number  of  Muslims  demonstrate  their  Islamic identity  in  Indonesia? This  country  has  attracted  imperialist  countries  to  colonize,  invade and plunder  its  resources.  Although  Indonesia  reached  its  independence  on  7 August  1945,  this country  still  witnesses  other  types  of  colonization  in  terms of  information  and  communication technology,  which  have  led  particularly  its Muslims  to  neglect  their  ‘Islamic  identity’  and generally  its  people  to neglect  their  predecessors’  efforts  to  obtain  the  freedom  of  this  country.DOI: 10.15408/insaniyat.v1i1.4389